Potential impact of combined inhibition of 3α-oxidoreductases and 5α-reductases on prostate cancer - Michael V. Fiandalo; Daniel T. Gewirth; James L. Mohler (Asian Journal of Urology)
Prostate cancer (PCa) growth and progression rely on the interaction between the androgen receptor (AR) and the testicular ligands, testosterone and dihydrotestosterone (DHT). Almost all men with advanced PCa receive androgen deprivation therapy (ADT). ADT lowers circulating testosterone levels, which impairs AR activation and leads to PCa regression. However, ADT is palliative and PCa recurs as castration-recurrent/resistant PCa (CRPC). One mechanism for PCa recurrence relies on intratumoral synthesis of DHT, which can be synthesized using the frontdoor or primary or secondary backdoor pathway. Androgen metabolism inhibitors, such as those targeting 5α-reductase, aldo-keto-reductase family member 3 (AKR1C3), or cytochrome P450 17A1 (CYP17A1) have either failed or produced only modest clinical outcomes. The goal of this review is to describe the therapeutic potential of combined inhibition of 5α-reductase and 3α-oxidoreductase enzymes that facilitate the terminal steps of the frontdoor and primary and secondary backdoor pathways for DHT synthesis. Inhibition of the terminal steps of the androgen metabolism pathways may be a way to overcome the shortcomings of existing androgen metabolism inhibitors and thereby delay PCa recurrence during ADT or enhance the response of CRPC to androgen axis manipulation. Keywords: Androstanediol, Dihydrotestosterone, Dutasteride, 3α-oxidoreductases, Androgen deprivation therapy, Abiraterone